2019
DOI: 10.3389/fimmu.2019.02627
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Interferon-γ and Vitamin D3 Signaling in Induction of ILT-3highPDL-1high Tolerogenic Dendritic Cells

Abstract: In the past, interferon (IFN)-γ and vitamin D3 (vit D3) have both been associated with induction of tolerogenic characteristics in human dendritic cells (DCs). Although there are only a few reports on interdependency of their actions, the interplay between IFN-γ and vit D3 has been clearly demonstrated in certain aspects of immune reactivity. Since both agents have been associated with regulation of immune responses, we set out to examine their functional and mechanistic interactions in context of principal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 43 publications
(47 reference statements)
0
21
0
1
Order By: Relevance
“…The active state of Vit D and IFN-γ are both pleiotropic endogenous immune modulators and may be useful in immunogenicity and immune tolerance. 23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active state of Vit D and IFN-γ are both pleiotropic endogenous immune modulators and may be useful in immunogenicity and immune tolerance. 23…”
Section: Discussionmentioning
confidence: 99%
“…The active state of Vit D and IFN-c are both pleiotropic endogenous immune modulators and may be useful in immunogenicity and immune tolerance. 23 Vit D prevents the development of autoantibody and reduces the number as well as the action of dendritic cell-related pathways, thus it causes suppression of T cell activation. Active vitamin D;1,25(OH)D has additional immunomodulatory activities, it prevents the proliferation of B cells before possessing the capacity to secrete immunoglobulin.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all inhibitory factors expressed by a DCreg necessarily contribute to the cell’s regulatory activities. Thus, vitamin D/IFNγ-induced human DCreg express IL-10, HLA-G, PD-L1 and low levels of FasL, but among these it was only their expression of PD-L1 that was reported as integral to the cell’s regulatory activities ( 60 ). It is also apparent that inhibitory receptors can play more than one role in immune tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…This inhibitory effect was occurred with the enhanced expression of CTLA-4, PD1 or PD-L1 on regulatory cells in the immune system, and also with the suppressive effect of IL-10, which is produced by Treg cells (28,29). Additionally, IFN- can synergistically enhance the suppression in proliferative responses with vitamin D3 by expressions of immunoglobulin-like transcript (ILT)-3 and programmed death ligand (PDL)-1 on tolerogenic DCs (30). In the present study, we observed reduced number of IFN- secreting Th lymphocytes in both drug-naïve and pSS treated patients, while the reduction was striking in drug-naïve patients.…”
Section: Discussionmentioning
confidence: 99%